Host parasiterelationships of Agaricus and Pleurotus spp. with Trichoderma harzianum Rifai isolates - Sobin, Femina; Diwan, Roly (Mushroom Research, 2019)
The major species of mushroom grown in India are white button mushroom, oyster mushroom and paddy straw mushroom. One of the most common and destructive diseases in mushroom cultivation is the green mould of which Trichoderma-spp. induce significant quantitative and qualitative losses in the mushroom cultivation.In the present study, isolates of pathogenic fungi Trichoderma harzianum-Rifai-and edible mushrooms (Agaricuscampestris, Pleurotus-ostreatus, P. florida and P. flabellatus) were paired in all possible combination in dual culture experiments to understand the antagonistic interactions of these fungi - on each other in vitro.Cases of green mould were reported to be caused byTrichodermaharzianum Rifai in Jabalpur area. This poses a threat to mushroom industries developing in Jabalpur.Dual culture experiments of Trichoderma-harzianum Rifai isolates with all the host mushrooms revealed that Trichodermaharzianum Rifai and the test host mushrooms are strongly antagonistic. In the total dual culture experimental set up 31.25% pairing shows deadlock on mycelial contact and 68.7% pairing shows overgrowth of pathogenic fungi on mushroom host after formation of initial deadlock.